2008
DOI: 10.1108/13619322200800021
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Framework for Goal‐directed Care within the Prison System

Abstract: A theoretical framework for goal-directed care within the prison system Bulten, E.; Vissers, A.; Oei, T.I. Published in: Mental Health Review Journal Publication date: 2008 Link to publication Citation for published version (APA):Bulten, E., Vissers, A., & Oei, T. I. (2008). A theoretical framework for goal-directed care within the prison system. Mental Health Review Journal, 13(3), 40-50. General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Within the penitentiary system, for instance, the issue of health is complicated, as prison is an environment characterised by order, discipline, and control rather than by care and cure [ 4 ]. Indeed, prison is mostly considered as a container of deviance, discomfort, pathologies, and addictions, and studies have demonstrated that, inside prisons, mental health is more vulnerable [ 5 , 6 ] and psychiatric pathologies are more prevalent [ 6 , 7 , 8 ] than in free society. The REDiME study [ 9 ] revealed that 58.7% of Italian prisoners currently experience psychiatric disorders, compared to only 8.7% of participants in a comparison group from the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the penitentiary system, for instance, the issue of health is complicated, as prison is an environment characterised by order, discipline, and control rather than by care and cure [ 4 ]. Indeed, prison is mostly considered as a container of deviance, discomfort, pathologies, and addictions, and studies have demonstrated that, inside prisons, mental health is more vulnerable [ 5 , 6 ] and psychiatric pathologies are more prevalent [ 6 , 7 , 8 ] than in free society. The REDiME study [ 9 ] revealed that 58.7% of Italian prisoners currently experience psychiatric disorders, compared to only 8.7% of participants in a comparison group from the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Offenders with mental illnesses have special needs that are not compatible with detention and the prison system [ 7 ]. Therefore, the inmate population and prison workers have had to live with various forms of psychological distress in a context that does not guarantee adequate space, training, medical/nursing resources, or psychological personnel to manage the new compliance system.…”
Section: Introductionmentioning
confidence: 99%